Towards an Endgame for the Cyprus Issue? Cyprus in the Aftermath of the Helsinki European Council - Tziampiris, Aristotle (Études helléniques / Hellenic Studies, 2001)
Cyprus has been on the forefront of international politics for almost half a century. Although overall the course of developments has not been positive for the Greek side, Cyprus’ relations with the European Union have been considerably more successful. These relations reached a new plateau at the December 1999 Helsinki meeting of the European Council. This article analyzes the potential significance, possible problems and recent developments linked to the Helsinki decisions. It is argued that for the first time since 1974, time is on the Greek side. This situation due is to the fact that Helsinki almost guarantees Cyprus’ eventual EU membership by not insisting on the prior solution of its political problem.